Bilateral Chronic Papilledema caused by Space Occupying Lesion: A Case Report: Poster Presentation - Case Report - Resident - BEATRICE MARIA POLUAN; STEVANUS PALILIEWU; ROBBY TUMEWU (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Papilledema is edema of optic disc due to raised intracranial pressure (ICP). Papilledema threatens both life and vision, therefore workup for the etiology of raised ICP is needed, including neuroimaging. Intracranial tumors cause increased ICP leads to papilledema. This case report caseof bilateral chronic papilledema as manifestation of space occupying lesion (SOL). Case Illustration : A 36 years old female presented with blurry black vision on the both eyes since 3 months ago. Complaints were felt suddenly with dominance on the left eye and accompanied with headache. Patient with 12 times history of motorcycle accidents without using helmet in the last 2 years. Funduscopy shows bilateral papilledema. MRI shows orbital within normal limit and solid lobulated mass extra-axial impression in the left posterior parietal region pressing on the left parietooccipital lobe with perifocal edema that obliterates the left lateral ventricle and results in a midline shift to the right. Neurosurgeon had planned for elective craniotomy tumor removal. Discussion : Increase in the total amount of intracranial tissue by SOL as underlying mechanism of raised ICP. SOL often causes intracranial hemorrhage, which frequently leads to papilledema. High ICP also produces a rise in CSF pressure surrounding the optic nerves leading to axoplasmic flow stasis, causing visual loss. High ICP due to SOL is typically treated surgically. Conclusion : This case explain that raised ICP caused by SOL leading to manifestation of papilledema.